An exploratory study on the differential diagnostic indicators between adult systemic EBV-positive T-cell lymphoproliferative disorders and angioimmunoblastic T-cell lymphoma with multiple EBV infections - Xiaodan Zheng; Yuanyuan Zheng; Yanlin Zhang; Jianlan Xie; Xiaojing Teng; Kuo Bi; Lan Sun; Xiaowen Huang; Mulan Jin; Xiaoge Zhou (Infectious Agents and Cancer)
Abstract Background The differential diagnosis between adult systemic EBV-positive T-cell lymphoproliferative disorders (EBV+ T-LPD) and angioimmunoblastic T-cell lymphoma (AITL) with multiple EBV infections is difficult, and distinguishing between the two has become a diagnostic challenge for pathologists. Given that the clinical treatment plans are different, an accurate diagnosis is a prerequisite to ensure effective treatment, therefore, it is extremely necessary and meaningful to find effective pathological indicators for distinguishing between two diseases. Methods We present a retrospective study comparing 7 cases of adult EBV+ T-LPD and 16 cases of AITL with multiple EBV infections diagnosed at our institution from 2017 to 2022. Differences in immunophenotype, type of EBV-infected cells, clonality and gene mutations between the two groups of cases were compared by immunohistochemical staining, double-label staining, TCR gene rearrangement and next-generation sequencing analysis. Results 7 cases of adult EBV+ T-LPD: all cases had no more than 1 T follicular helper (THF) marker was expressed, and there were significantly more EBER+/CD3 + cells than EBER+/CD20 + cells; 5 cases had mutation detection results, in which only 1 had the characteristic KMT2D mutation, 2 had TET2 mutations, and no common mutations such as DDX3X were detected.16 cases of AITL with multiple EBV infections: all cases were found to express at least 2 TFH markers, with 87% of them expressing at least 3 TFH markers., and had significantly more EBER+/CD20 + cells than EBER+/CD3 + cells; 4 cases had mutation test results, with mutated high-frequency genes being TET2 (100%, and all of them had 2 or more TET2 mutations) and RHOA G17V (100%), DNMT3A mutation occurred in 2 cases (50%), and IDH2 R172 mutation occurred in 1 case (25%). Conclusions We found that the expression pattern of TFH markers, the types of cells predominantly infected by EBV and the different mutations can all be used as effective pathological indicators for distinguishing between two diseases.